Optimalisasi Manajemen Inventori melalui Pelatihan dan Peningkatan Kemampuan Memanfaatkan Olsera dalam Pencatatan Stok Barang pada UMKM secara Online - Mas'ud, Syamsuddin; Ramadana, Yusuf (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Inventory data inaccuracy is a common issue faced by many UMKM, especially those operating in the food and beverage (F&B) industry. One effective solution to address this problem is implementing proper inventory management using digital tools such as the Olsera application. This community service project aimed to optimize inventory management by providing training and improving employees' skills in using Olsera for inventory recording. The project was carried out in four stages: discussions with the partner, preparation, training implementation, and monitoring and evaluation. As a result of these activities, the partner’s ability to use Olsera improved significantly, a standardized inventory recording process was established, and inventory data inaccuracies were reduced.